Supercritical fluid extraction of oil from Mahkota dewa seed - Sarker, Md Zaidul Islam; Azmir, Jannatul; Khan, Md Sharif; Ferdosh, Sahena (ISTEC, 2014)
Mahkota dewa (Phaleria macrocarpa) which belongs to Thymelaeaceae family is being used as medicinal plant in tropical countries especially in Malaysia and Indonesia. Almost all parts of this plant except seed have importance in traditional medicine. The seed contains high amount of oil. In this study, solvent extraction and supercritical fluid extraction using carbon dioxide were used to extract oil from the Mahkota dewa seed. The effecting parameters of supercritical carbon dioxide extraction were optimized for obtaining higher yield of oil by response surface methodology (RSM) with central composite design (CCD). By solvent extraction, more than 55g per 100g of dry weight of seed was obtained whereas at optimum condition of supercritical fluid extraction, the oil yield was around 53g per 100g of dry weight of seed. However, the purified oil was extracted by SFE that is of organic residues free. The triglycerides in terms of fatty acid constituents of the extracted oil were analyzed by gas chromatographymass spectroscopy (GC-MS). The extracted oil found to have 73% unsaturated fatty acids and 26% saturated fatty acids. Polyunsaturated fatty acids were in the percentage of 36.25%. Thus, the supercritical CO2 extracted Mahkota dewa (P. macrocarpa) seed oil of could be claimed as high quality and toxic free food and pharmaceutical grade oil.